Innovation in mother and child care in the hospital and community - Septiani, Diah (Innovation in Health for Society, 2023)
It is possible for essential measures to enhance the outcomes of maternal and newborn health (MNH) in countries with low and intermediate incomes; however, the implementation of these interventions has proved difficult. The value that innovative MNH techniques provide to existing health systems is still only partially recognised, despite the fact that they have the potential to hasten the pace of improvement and lead to improved health outcomes for pregnant women and newborns. Future implementation and evaluation initiatives will need to determine how innovations affect the outcomes of health care and give evidence regarding the possibility for scale-up, taking into account factors such as cost, feasibility, appropriateness, and acceptability. Measurement of equity is a critical component in locating and focusing on segments of the population who are at increased risk of experiencing service disparities. In order for innovative MNH interventions to be successfully integrated into existing health care systems, there will need to be innovative techniques for their implementation, assessment, and expansion. The Innovations for Maternal, Newborn, and Child Health initiative was a multi-year grant led by Concern Worldwide to find and test ambitious new ideas with the potential to overcome barriers to accessing maternal, newborn, and child health (MNCH) services and significantly improve delivery of these services. The initiative was called the Innovations for Maternal, Newborn, and Child Health (IMNCH) Challenge. Keywords: Maternity care; health innovation; healthcare; quality of care; maternal safety